STRATEGI BRAND MARKETING FAS DALAM MENINGKATKAN AWARENESS DI INSTAGRAM @fas.fulfillment - Anggi Dwi Kusumawardani; Hudi Santoso (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
The background of this research lies in the growing role of social media particularly Instagram as a strategic platform for companies to build a credible and engaging brand image, especially for B2B-based businesses like FAS. This study aims to analyze the brand marketing strategy of FAS in enhancing brand awareness through its Instagram account @fas.fulfillment. This study applies a descriptive qualitative approach through in-depth interviews with the FAS brand marketing team and content analysis of the brand’s Instagram account. The findings indicate that FAS’s brand marketing strategy focuses on balancing entertaining and educational content with a light, relatable, and visually consistent communication style. “Pak Bos”-themed and Gen Z–related posts generated the highest engagement, showing the audience’s preference for humorous and authentic storytelling. The application of the AISDALSLove model is evident from the attention to love stages, where audiences not only consume the content but also engage, share, and build emotional attachment to the brand. This strategy demonstrates that human-centered, consistent, and storytelling-driven communication effectively strengthens FAS’s image as a modern, adaptive, and audience-oriented fulfillment service provider.